2006
DOI: 10.1007/s10562-005-9191-6
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Acidity of the Double-function Catalyst for DME Synthesis from Syngas

Abstract: Two kinds of HZSM-5 zeolite (SiO 2 /Al 2 O 3 =50,300) were introduced into the STD (syngas-to-DME) reaction and the doublefunction catalysts containing CuO/ZnO/Al 2 O 3 and HZSM-5 were investigated by activity evaluation and NH 3 -TPD. It was found that the acidity of HZSM-5 played a critical role in the performance of STD catalyst, and an appropriate acidic amount was required to obtain the best activity of STD catalyst; more and less acidic amount were both unfavorable for DME yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 15 publications
(18 reference statements)
1
37
0
1
Order By: Relevance
“…The catalysts exhibiting activities in 1-butene double-bond-shift isomerization reaction had an evident desorption peak of ammonia around 100°C. The peak can be assigned to NH 3 weak acid sites [30,31]. The peak area broadly increased with the yield of 2-butene enhanced, suggesting the surface weak acid sites have positive impacts on the catalytic performances as reported [32][33][34].…”
Section: Effect Of the Surface Acidity On Catalytic Performancementioning
confidence: 99%
“…The catalysts exhibiting activities in 1-butene double-bond-shift isomerization reaction had an evident desorption peak of ammonia around 100°C. The peak can be assigned to NH 3 weak acid sites [30,31]. The peak area broadly increased with the yield of 2-butene enhanced, suggesting the surface weak acid sites have positive impacts on the catalytic performances as reported [32][33][34].…”
Section: Effect Of the Surface Acidity On Catalytic Performancementioning
confidence: 99%
“…Here a relatively small amount of acid sites were sufficient to convert methanol into DME as the rate of dehydration due to HZSM-5 (80) is much faster than the methanol formation rate (rapid transformation of methanol to DME). Wang et al [48] used two kinds of HZSM-5 zeolite in the STD at different (SiO 2 /Al 2 O 3 ) ratio with CuO/ZnO/Al 2 O 3 . They found that the acidity of HZSM-5 played a critical role in the performance of STD catalyst, and that an optimal acidic amount was required to obtain the best activity of STD catalyst; more and less acidic amounts were both unfavourable for DME.…”
Section: Cza/hzsm-5(80)mentioning
confidence: 99%
“…Furthermore, zeolites are more resistant than -Al 2 O 3 towards poisoning of acid sites by the water by-product [4,5,6]. Among the zeolites, the medium pore ZSM-5 (MFI) has been by far the most widely applied as the acid component in bifunctional DME synthesis catalysts [5,7,8,9,10,11], though other zeolites such as ferrierite, MCM-22 and its delaminated counterpart ITQ-2, IM-5, and TNU-9 have also been investigated [12,13].…”
Section: Introductionmentioning
confidence: 99%